EFEKTIVITAS TERAPI MUROTTAL AL-QUR’AN TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF - Yana, Rahma '; Utami, Sri '; ', Safri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Pain during childbirth is a physiologic condition. Labor pain can be treated by using pharmacologically and nonpharmacologically theraphy. One of the non-pharmacologically theraphy that can be used to reduce labor pain is Murottal Al-Qur’an. This study aimed to find the effectiveness of murrotal Al-Qur’an theraphy on the labor pain intensity at the first stage of active phase. This study used Quasy experiment research design with non-equivalent control group design. The research samples were 30 respondent which were divided into experiment group and control group. The research was done on maternal mother on her first stage of active phase in Petala Bumi Regional Public Hospital. The amount of sample were 30 people which were choosen using purposive sampling technique while keeping the inclusion criteria on mind. The measurement instrument used was NRS (Numeric rating scale). The analyses used were univariate and bivariate analysis using independent sample T test and dependent sample T test. The result of of the study showed that the average labor pain intensity after murottal Al-Qur’an theraphy was given to the experiment group was 6,40 and on the control group which was not given murottal Al-Qur’an theraphy was 7,40. The statistical result was p value (0,018) < α (0,05), therefore it can be concluded that murottal Al-Qur’an theraphy is effective to lower labor pain intensity at the first stage of active phase and it is recommended to become the intervention when treating labor pain. Keywords: Murottal Al-Qur’an, pain of labor